(untitled) (International Journal of Medical and Surgical Sciences, 2014)
The somite or phylotypic period is similar in many vertebrate species from fish to man. Somites consist of thickening of the mesoderm, they simultaneously form in pairs, one on each side of the notochord. In the human embryo formation of somites is initiated on day 20, resulting in a total of three pairs of somites per day with a total of 44±2 pairs of somites. Somite formation occurs where the FGF -8 is at a low threshold. Positional somites identity is specified by the combined expression of the Hox gene complex. Somites give rise to axial skeleton (vertebrae and ribs), all skeletal muscles including members of the body wall and also most of the dermis. The WNT protein induces muscle precursor cells from the dorso medial portion of the somite and MIF5 gene expression. The somite dermatome dermis becomes action neurotrofina3 (NT -3) secreted by the dorsal neural tube. Sonic hedgehog protein produced by the notochord and neural tube induces sclerotome formation, from somite ventrally and the expression of PAX 1 which in turn, controls the formation of chondrogenesis and vertebrae.